2021
DOI: 10.3389/fmicb.2021.601061
|View full text |Cite
|
Sign up to set email alerts
|

Holstein and Jersey Steers Differ in Rumen Microbiota and Enteric Methane Emissions Even Fed the Same Total Mixed Ration

Abstract: Previous studies have focused on the rumen microbiome and enteric methane (CH4) emissions in dairy cows, yet little is known about steers, especially steers of dairy breeds. In the present study, we comparatively examined the rumen microbiota, fermentation characteristics, and CH4 emissions from six non-cannulated Holstein (710.33 ± 43.02 kg) and six Jersey (559.67 ± 32.72 kg) steers. The steers were fed the same total mixed ration (TMR) for 30 days. After 25 days of adaptation to the diet, CH4 emissions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“…VFA production is negatively correlated with ruminal pH [44]. In this study, the ruminal pH and total VFA were not influenced by trace mineral supplementation; however, lower ruminal pH was recorded in Jersey steers than in Holstein steers, which is in agreement with the findings of Islam et al [45]. This might be due to the higher total VFA production by Jersey steers compared to that by Holstein steers in this study.…”
Section: Discussionsupporting
confidence: 91%
“…VFA production is negatively correlated with ruminal pH [44]. In this study, the ruminal pH and total VFA were not influenced by trace mineral supplementation; however, lower ruminal pH was recorded in Jersey steers than in Holstein steers, which is in agreement with the findings of Islam et al [45]. This might be due to the higher total VFA production by Jersey steers compared to that by Holstein steers in this study.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that the rumen microbiota was disturbed due to the feeding of high concentrate ( Krause and Oetzel, 2006 ; Moya et al, 2009 ), the rumen microbiota underwent value-added, together with the composition of the diet and the special breed of yaks, this resulted in a higher abundance and diversity of rumen microbiota in the C80 group of yaks. PCoA analysis showed that rumen microbiota clustered according to different dietary concentrate ratios and significant differences between rumen microbiota were observed, which is consistent with other studies ( Hu et al, 2019 ; Islam et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that feeding high concentrate diets to yaks causes a decrease in rumen pH and inhibition of cellulose-degrading bacteria, leading to a decrease in the diversity and abundance of ruminal bacteria. PCoA analysis showed that rumen microbial communities aggregated according to the concentrate ratio in diets, and significant differences between intra-ruminal microbial communities were observed, which were consistent with previous reports ( Hu et al, 2019 ; Islam et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%